Factors associated with the quality of service in Peruvian public hospitals - Álvaro Danny Benites Bernabé; Ericson Felix Castillo Saavedra; Cinthia Rosales Márquez; Rosa María Salas Sánchez; Cecilia Elizabeth Reyes Alfaro (Medisur)
Background: It is very important that health teams are prepared to provide care according to the required needs, and with this, meet the expectations of users. This is the basis of the interest in user care quality studies in the health context. Objective: to determine the factors associated with the quality of the service in Peruvian public hospitals. Methods: descriptive study, which included 210 patients treated in two hospitals in the province of Santa, Peru. A 22-item instrument based on the SERVQUAL model was used. Inferential analysis was performed based on the normality of the data, to establish a significant difference between the dimensions of the quality of service for the hospitals under study. Likewise, to evaluate the association between the factors and the quality of the service, the Pearson bivariate correlation test was used. Results: the level of quality was high (62%) and medium (78%) for the La Caleta and Eleazar Guzmán Barrón hospitals, respectively. There was a difference in the quality of the service, represented by the dimensions of reliability, responsiveness, security, empathy and tangible elements. In the correlation analysis, only in the Eleazar Guzmán Barrón Hospital was a significant and positive association found between the type of user and the quality of service. Conclusion: the quality of the service provided in outpatient clinics behaves in a variable way among public hospitals, being only dependent on the type of user attended.